(454) Social Change and Growth - R. M. Poduval (معهد التخطيط القومى, 2026)
This study examines the role of agriculture as a fundamental component of economic development, with particular emphasis on developing and African countries. It argues that agriculture serves as a major source of national income, employment opportunities, and export earnings, making agricultural development a critical requirement for sustainable economic growth. The study highlights that economic development is characterized by a gradual transition from traditional subsistence farming systems, which primarily satisfy household needs, toward commercial agriculture that is increasingly oriented toward market production .The study indicates that rapid population growth, urbanization, and rising income levels contribute significantly to increasing demand for food products and agricultural commodities. Consequently, expanding agricultural production and improving its efficiency become essential requirements for meeting market needs. The transition from subsistence farming to commercial agriculture requires substantial structural changes in agricultural systems, including the development of transportation and marketing infrastructure, reform of land tenure systems, and the provision of adequate price incentives for farmers. Furthermore, the study emphasizes the importance of agricultural productivity as a driving force for economic growth. Increased labor productivity in agriculture facilitates the transfer of labor from agricultural activities to other economic sectors, particularly industrial and service sectors. The research also demonstrates that the success of this structural transformation depends on several factors, including population growth rates, the pace of expansion in non-agricultural sectors, and the production technologies employed. The study concludes that education and manpower planning play essential roles in agricultural and economic development. Educational and training programs contribute to preparing the technical, administrative, and professional workforce necessary for implementing agricultural development initiatives. The findings suggest that investment in human resources and educational planning should be regarded as integral components of comprehensive development strategies aimed at promoting economic transformation, enhancing productivity, and achieving sustainable growth.